Application of Generative Learning Methods In Arabic Lessons To Improve Students' Reading Skills/ تطبيق طريقة التعليم التفسيري في درس اللغة العربية لترقية مهارة القراءة لدى الطالبات - Dewi Nur Laili (State Islamic University (UIN) of Sunan Ampel Surabaya, Indonesia, 2021)
Abstract This research applies Generative learning methods using quantitative method research and the research model was experimental research. The researcher sets the alternative hypothesis (Ha), that there is a relationship between the application of Generative learning methods (Variable X) with the reading skills of students (Variable Y). And vice versa for the final hypothesis (Ho). With uses data collection methods as follows: Observation, Interview, Questionnaire and Test. The application of Generative learning methods is an appropriate method to be applied and effective. The effectiveness of the application of this method can be seen from the results of research data analysis that the value of T Calculate (t0) 10.72 is greater than T Table (tt) 2.861, this indicates that (Ho) is rejected and (Ha) is accepted. And the conclusion of this study is the existence of strong effectiveness with the application of Generative methods to improve the reading skills of students.